Predictive Role of Neutrophil to Lymphocyte Ratio in Adnexal Torsion: A Systematic Review and Meta-Analysis - Shokoufeh Khanzadeh; Hossein Tahernia; Jairo Hernandez; Camila Sarcone; Brandon Lucke-Wold; Amirhosseinn Salimi; Fatemeh Tabatabaei (Mediators of Inflammation)
Introduction. The goal of this systematic review and meta-analysis was to consolidate the available data on the role of the neutrophil to lymphocyte ratio (NLR) in predicting adnexal torsion (AT), to help guide clinical decision-making and outcomes. Methods. We used Web of Science, PubMed, and Scopus to conduct a systematic search for relevant publications published before June 26, 2022. We reported standardized mean difference (SMD) with a 95% confidence interval (CI). Because a significant level of heterogeneity was found, we used the random-effects model to calculate pooled effects. We used the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) too for quality assessment. Results. Overall, 15 articles were included in the analysis. A random-effects model revealed that patients with AT had elevated levels of NLR compared to those with other adnexal masses (SMD=1.06, 95%CI=0.67 to 1.45, p<0.001). So, NLR had diagnostic value. In the subgroup analysis according to ethnicity, we found that Caucasian patients with AT had elevated levels of NLR compared to patients who were operated due to adnexal mass and reported as having a benign ovarian cyst, without torsion (SMD=1.12, 95%CI=0.71 to 1.54, p<0.001). However, in the case of East Asian patients, there was no difference between cases and controls (SMD=0.86, 95%CI=−0.21 to 1.94, p=0.11). The pooled sensitivity of NLR was 0.79 (95%CI=0.72–0.85), and the pooled specificity was 0.84 (95% CI, 0.74–0.91). Conclusion. In conclusion, there has been an interest in the use of NLR as a diagnostic marker for AT.